IMPLEMENTASI KURIKULUM 2013 DALAM PEMBELAJARAN PPKN DI SMA NEGERI SE KOTA PEKANBARU - Muhammad Syahroi Syahroi; Gimin '; Zahirman ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:This research was motivated by the implementation of Curriculum 2013 in PPKn learning process. Education is an absolute must for everyone where it will form a strong, qualified, authoritative, and have a knowledge and ability to live in accordance with the times. Throughout the history of curriculum development in Indonesia, Curriculum 2013 development was the most remarkable pro-contra. Curriculum improvement is actually a common thing, even in fact it is a necessity. It motivated the writer to take a title “The Implementation of Curriculum 2013 in PPKn Learning Process in Senior High Schools throughout the City of Pekanbaru”.The formulation of the research are as follow: “How is the implementation of Curriculum 2013 in PPKn learning process?” and “How is the difficulty level faced by PPKn teachers in Curriculum 2013?”. The objectives of the research are to find out the implementation of Curriculum 2013 in PPKn learning process and to find out the difficulty level faced by PPKn teachers in Curriculum 2013. The population of the research was 6 schools which implement Curriculum 2013, and the sample of the research was 15 PPKn teachers. The instrument to collect the data were questionnaires which consist of 76 questions, and interviews which consist of 4 questions. The data were analyzed by Qualitative Descriptive through percentage. Based on the calculation of percentage by respondents, the  answer “often” was obtained as 53,78376% placed on rank 34%-66% that was adequate. Thus, the hyphothesis which explains the PPKn teachers who were “adequate” toward the implementation of Curriculum 2013 in PPKn learning proces, was accepted. Based on the research findings, it can be inferred that a study on the PPKn teachers toward the implementation Curriculum 2013 in Senior High Schools throughout the city of Pekanbaru were adequate. Keywords: The Implementation of Curriculum 2013.